Надежды и радости: Роман / Э. Дин; Пер. с англ. В. А. Сазанова - Дин Элисса (Очарование, 2002)
Экземпляры: ф.18 (2012) / Инвентарный номер: 49195 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Д 46 / ББК: 84(7Сое)